Effect of Interest Rate and Exchange Rate on Volatility of Market Index at Nepalese Stock Exchange - Shakya, Aaryan Ratna (Nepalese Journal of Finance, 2025)
This study examines the impact of fundamental factors on market index volatility in Nepalese commercial banks and finance companies. Market index volatility is the selected dependent variable. The selected independent variables are bank rate, deposit interest rate, lending interest rate, base rate and inflation rate. The study is based on secondary data of 7 commercial banks and 3 finance companies with 100 observations for the study period from 2012/13 to 2021/22. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks and finance companies. The correlation coefficients and regression models are estimated to test the significance and importance of bank rate, deposit interest rate, lending interest rate, base rate and inflation rate. The study showed that bank rate has a negative impact on market index volatility. It means that increase in bank rate leads to decrease in market index volatility. In addition, deposit interest rate has a negative impact on market index volatility. It indicates that increase in deposit interest rate leads to decrease in market index volatility. Similarly lending interest rate has a negative impact on market index volatility. It indicates that increase in lending interest rate leads to decrease in market index volatility. Further, the study also showed that base rate has a negative impact on market index volatility. It means that higher the base rate, lower would be the market index volatility. Moreover, inflation rate has a negative impact on market index volatility. It shows that higher the inflation rate, lower would be the market index volatility.